PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH, DAN DANA ALOKASI UMUM TERHADAP PENGALOKASIAN BELANJA MODAL PADA KABUPATEN HUMBANG HASUNDUTAN TAHUN 2017-2021 - Saragih, Joana L.; Lumban Gaol, Ruminta (Jurnal Riset Akuntansi & Keuangan, 2023)
This study aims to determine the effect of economic growth, local revenue and general allocation funds on the allocation of capital expenditures in Humbang Hasundutan district in 2017-2021. The data collection technique used is documentation technique. The data analysis technique used is multiple linear regression analysis technique, namely to determine the relationship between the independent variable and the dependent variable.The results of this study partially show that economic growth has no significant positive effect on capital expenditures. This is indicated by the value of t arithmetic < t table where 0.512 < 1.687 with a significance level of 0.611 > 0.05, local revenue has a significant positive effect on capital expenditure. This is indicated by the value of tcount 0.949> ttable 1.687 with a significant value of 0.048 <0.05, general allocation funds have an insignificant negative effect on capital expenditure. This is indicated by . tcount -0.545 < ttable 1.687 with a significant value of 0.589 > 0.05. Simultaneously, economic growth, local revenue and general allocation funds have no significant effect on capital expenditure, this is indicated by a significant value of 0.778 > 0.05 and Fcount 0.366 < Ftable 2.852.